Long‐term observational study of afamelanotide in 115 patients with erythropoietic protoporphyria. (30th April 2015) - Biolcati, G.; Marchesini, E.; Sorge, F.; Barbieri, L.; Schneider‐Yin, X.; Minder, E.I.
Summary Background In erythropoietic protoporphyria (EPP), an inherited disease of porphyrin‐biosynthesis, the accumulation of protoporphyrin in the skin causes severely painful phototoxic reactions. Symptom prevention was impossible until recently when afamelanotide became available. Afamelanotide‐induced skin pigmentation has statistically significantly improved light‐tolerance, although the clinical significance of the statistical effect was unknown. Objectives To assess clinical effectiveness by recording compliance and safety during prolonged use. Methods We report longitudinal observations of 115 ambulatory patients with EPP, who were treated with a total of 1023 afamelanotide implants over a period of up to 8 years at two porphyria centres; one in Rome, Italy, and the other in Zurich, Switzerland. Results Since the treatment first became available in 2006, the number of patients treated with 16 mg afamelanotide implants rose continuously until June 2014, when 66% of all patients with EPP known to the porphyria centres were treated. Only three patients considered afamelanotide did not meet their expectations for symptom improvement; 23% discontinued the treatment for other, mostly compelling, reasons such as pregnancy or financial restrictions. The quality of life (QoL) scores, measured by an EPP‐specific questionnaire, were 31 ± 24% of maximum prior to afamelanotide treatment, rose to 74% after starting afamelanotide and remained at this level during the entire observation period. Only minor adverse events attributable to afamelanotide, predominantly nausea, were recorded. Conclusion Based on the improved QoL scores, high compliance and low discontinuation rates, we conclude that afamelanotide exhibits good clinical effectiveness and good safety in EPP under long‐term routine conditions.